Aging Labor and Japanese Industry Performance: Lessons for Indonesia Policies - Indri Dwi Apriliyanti (Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
This study analyzes the labor input factor that determines and shapes output generation in Japan. It hypothesizes that labor input contributes to the development of output growth in Japanese industries. In addition to that, it is hypothesized that moderator variable which is represented by numbers of aging labor can either stimulate or weaken the output generation. Hypotheses are tested using the data obtained from the Research Institute of Economy, Trade, and Industry (RIETI) Japan Industrial Output (JIP) Database 2011 and Japan Statistics Oﬃcial within period 1970 to 2008. A multiple regression analysis, a manova and a hierarchical multiple regression analysis are conducted. Similar to expectation, aging labor has a negative moderating eﬀect on labor-intensive industry; meanwhile aging labor has a positive moderating eﬀect on capital-intensive industry. Not only does this study provide thorough knowledge towards output generation in Japan, but it also provides substantial lessons for Indonesia, particularly to enhance the industrial policy regarding the aging labor.